2015
DOI: 10.1093/femspd/ftu024
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori induces IL-1β and IL-18 production in human monocytic cell line through activation of NLRP3 inflammasome via ROS signaling pathway

Abstract: This study investigated whether Helicobacter pylori could activate the nucleotide-binding oligomerization domain-like receptor (NLR) family, pyrin domain-containing 3 (NLRP3) inflammasome in human macrophages and the involvement of reactive oxygen species (ROS) in inflammasome activation. Phorbol-12-myristate-13-acetate (PMA)-differentiated human acute monocytic leukemia cell line THP-1 was infected with H. pylori. The levels of pro-inflammatory cytokines interleukin (IL)-1β and IL-18 in supernatant were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…This effect was observed in the early events post-infection [115], suggesting that the oxidative burst, rather than the effect of SMOX is involved. These results are also consistent with in vitro data showing that the partial scavenging of ROS by N-acetylcysteine led to a decrease of H. pylori -induced inflammasome formation and production of IL-1β and IL-18 by the human monocytic cell line THP-1 [116]. …”
Section: Endogenous Effect Of Ros On the Hostsupporting
confidence: 91%
“…This effect was observed in the early events post-infection [115], suggesting that the oxidative burst, rather than the effect of SMOX is involved. These results are also consistent with in vitro data showing that the partial scavenging of ROS by N-acetylcysteine led to a decrease of H. pylori -induced inflammasome formation and production of IL-1β and IL-18 by the human monocytic cell line THP-1 [116]. …”
Section: Endogenous Effect Of Ros On the Hostsupporting
confidence: 91%
“…In contrast, a second study reported that gp91 phox−/− mice exhibit more inflammation and increased monoculear cell infiltration in the mucosa during infection with H. felis or H. pylori (Blanchard et al 2003). Although this investigation was performed at 3-weeks post-infection, which is not sufficient time to observe strong gastric inflammation, the results are consistent with in vitro data showing that the partial scavenging of ROS by N-acetylcysteine led to a decrease of H. pylori -induced inflammasome formation, and IL-1β and IL-18 production by H. pylori -infected THP-1 cells (Li et al 2015). …”
Section: Induction and Role Of Rossupporting
confidence: 86%
“…Indeed, recent several studies reported the signaling pathways for IL-1β production (16,19,29). However, the detailed mechanism of H. pylori-mediated IL-1β induction remains fully clarified.…”
Section: Quantitative-rt-pcrmentioning
confidence: 99%